New Graduate Nurses Navigating Entry to Practice in the Covid-19 Pandemic. Issue 1 (March 2023) - McMillan, Kim; Akoo, Chaman; Catigbe-Cates, Ashley
Background: The Covid-19 pandemic has significantly impacted organizational life for nurses, with known physical and psychological impacts. New graduate nurses are a subset of nurses with unique needs and challenges as they transition into their registered nurse roles. However, this subset of nurses has yet to be explored in the context of the Covid-19 pandemic. Purpose: To explore the experiences of new graduate nurses entering the profession in Ontario, Canada, during the Covid-19 pandemic approximately one year after entering the profession. Methods: Thorne's interpretive description method was utilized. Findings: All participants identified as completing second entry nursing programs, offering a unique perspective on new graduate nurse transition. Four themes emerged in the data: ' Virtual Didn't Cut It, ' 'Go Where You Know, ' 'Picking Up the Pieces, ' and 'Learning When to Say No and Let Go.' Participants felt ill prepared to enter the profession and were cognizant of the various challenges facing the nursing profession, and how these pre-existing challenges were exacerbated by the pandemic. They acknowledged the need to protect themselves against burnout and poor mental health, and as such, made calculated early career decisions – demonstrating strong socio-political knowing. Half of the participants had already left their first nursing job; citing unmet orientation, mental health, and wellbeing needs. However, all participants were steadfast in remaining in the nursing profession. Conclusions: Second entry new graduate nurses remain a unique subset of nurses that require more scholarly attention as their transition experiences may differ from the traditional trajectory of new graduate nurses.